Flex-nucleoside analogues – Novel therapeutics against filoviruses. Issue 12 (15th June 2017) - Yates, Mary K.; Raje, Mithun R.; Chatterjee, Payel; Spiropoulou, Christina F.; Bavari, Sina; Flint, Mike; Soloveva, Veronica; Seley-Radtke, Katherine L.
Graphical abstract: Abstract: Fleximers, a novel type of flexible nucleoside that have garnered attention due to their unprecedented activity against human coronaviruses, have now exhibited highly promising levels of activity against filoviruses. The Flex-nucleoside was the most potent against recombinant Ebola virus in Huh7 cells with an EC50  = 2 μM, while the McGuigan prodrug was most active against Sudan virus-infected HeLa cells with an EC50 of 7 μM.